Studi korelasi tubex positif dengan indeks eritrosit pada penderita demam tifoid di RSUD Aceh Tahun 2023 - Safwan, Safwan; Hadijah, Siti; Rahmayanti, Rahmayanti (Poltekkes Kemenkes Aceh, 2024)
Background: Diagnosis of typhoid fever can be done by tubex examination. Hematological changes occur in typhoid fever due to bone marrow suppression. The patient's hemoglobin decreased slowly to the point of anemia. Erythrocyte indices, namely mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC), are used to classify anemia.Objectives: To determine the correlation between the degree of tubex positivity and the erythrocyte index in patients suffering from typhoid fever at the Aceh Regional General Hospital in 2023.Methods: Observational analytic with cross-sectional design. The sampling method was purposive sampling, inclusion criteria: respondents who underwent tubex examination and erythrocyte index. The research data is secondary data from regional general hospital medical record.Results: Based on Spearman's correlation, MCV has a very weak relationship with a positive patterned correlation, and MCHC has a very weak relationship with a negative patterned correlation where MCHC values decrease with an increase in the degree of tubex positivity.Conclusion: Typhoid fever sufferers may experience changes in the size of their erythrocytes to become larger, even though typhoid fever sufferers do not experience anemia. KeywordsTifoid fever, tubex, erytrocyte indices